The Status of Mother Tongue Use in English Language Teaching in the Kurdish Context: Students’ Perspective - Kawa Qadir Muhammad; Qani Nasih Najim (Zanco Journal of Humanity Sciences)
This study is centered around the prevalent and ongoing debate on using students’ mother tongue in English language teaching. Therefore, this study is aimed at exploring the current status of Kurdish language use in the target high schools as typical EFL teaching contexts in the Erbil province of the Iraqi Kurdistan Region where up-to-date research is not available. The study further investigates the sample high school students’ attitudes towards their mother tongue use in preferred English teaching practices. Achieving these aims was approached through a mixed method approach where both qualitative (field observation notes) and quantitative (students’ questionnaire) data collection tools were utilized. The ‘field notes’ were utilized to record the observed mother tongue functions and purposes in the classroom. Whereas the questionnaire was used to elicit students’ perceptions and attitudes towards using Kurdish as their mother tongue in English teaching practices. Among the outstanding findings of the study is that students’ expectations for mother tongue use are satisfied in the sample high school teaching practices. In addition, the purposes for which their mother tongue is used cover various areas, including facilitating language teaching, maintaining classroom discipline, and fostering a secure psychological atmosphere in the classroom.